A novel technique for repairing a large diaphragmatic defect with no costal attachments. (17th April 2013) - Tucker, Adam; Parissis, Harry
Abstract : Chronically ruptured diaphragms are difficult to diagnose. Often they are asymptomatic but convey a high risk for incarceration, and therefore surgical repair is mandatory. In the following case report, we present an abnormal 10×12 cm diaphragmatic defect whereby there was no anterior edge to the defect. This posed a challenge as to how to repair. We present a novel technique that facilitates sound solution through a thoracotomy approach.